ANALYSIS OF STUDENT'S ERROR IN PROBLEM-SOLVING ON THE SOCIAL ARITHMETIC MATERIAL - Mira Amalia Yudhanti; Nur Arina Hidayati (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2019)
Based on the author's observation, many students have difficulty in solving the story problem. This study aims to determine student errors and the causes of student error using the Polya method. Polya error analysis is a method used to analyze mistakes made by students with four stages. This research is qualitative research with a type of descriptive research. This research is the students of class VII-B State Junior High School (SMP N) 5 Banguntapan Bantul. The object of this research is the student's mistake in solving the problem based on Polya. Data collection techniques in this research are problem-solving and interview. According to Miles and Huberman, data analysis techniques using data analysis, namely data reduction, data presentation, and conclusion. The results showed that the types of students' mistakes made by the research subjects on solving problem question of social arithmetic form were 50% misconceptions, 65% for made a settlement plan, 70% for executed a settlement plan, and reviewed the process and results by 65%. The most common mistake is at the stage for executed a settlement plan. Factors that cause errors are made because students are not careful in problem-solving.